Bipesticides: effective alternative to organic Nepal - GC, Yubak Dhoj (Journal of Agriculture and Environment, 2015)
Historically agriculture has been the major -culture to the majority of the Nepalese people, however, in recent days, the trend is gradually shifting towards other sectors like business and services. The dependency on agriculture both on direct and indirect has been declining from 90% to 65%, indicating towards its specialization, commercialization and diversification. This has further necessitated to the high input based agriculture, especially chemical fertilizers, pesticides and seeds. At the same time, considerable interests are pounding on the organic agriculture. This fact has becoming evident due to growing demands of organic produce within and outside the country. Nepal can earn money by producing and exporting of organic agricultural produce to its neighboring countries- China and India. In this context, Nepal is situated on the strategic point where it may take the advantages from the flourishing economy of its giant neighbors. Nepal can choose natural farming as well to rely on the use of biorational compounds like biopesticides for combating biotic and abiotic stresses. Very importantly, such products need producing within the home country and are made accessible to the farmers.